Hamstring muscle strain - Askling, C. (2008)
Background: Acute hamstring strains are common injuries in different sports. They are often serious, causing long rehabilitation times and a proneness for re-injury. Preliminary observations indicate that the injuries can be of at least two types, one occurring during high-speed running and the other during motions where the hamstring muscles reach extreme lengths.